A budget impact model and a cost–utility analysis of reducer device (Neovasc) in patients with refractory angina - Fortunato, Agostino; Valentini, Ilaria; Rumi, Filippo; Antonini, Debora; Siviero, Ludovica; Di Brino, Eugenio; Basile, Michele; Cicchetti, Americo (Frontiers in Cardiovascular Medicine, 2024)
Background: Refractory angina is a chronic condition characterized by the presence of debilitating angina symptoms due to established reversible ischemia in the presence of obstructive coronary artery disease. Treatments for this condition have undergone major developments in recent decades, however, the treatment of refractory angina is still a challenge for medicine. In this sense, the Coronary Sinus Reducer System stands as the last line of therapy for ineligible patients for revascularization with reversible ischemia. The purpose of this report is to evaluate the potential burden on the National Health Service and measure health effects in terms of both quantity (life years) and quality of life aspects related to the Reducer. Methods: Two different economic evaluation models were developed as part of the analysis. The budget impact was developed with the aim of estimating the potential burden on the National Health Service from incremental uptake of Reducer use in the target population. The utility cost analysis compares and evaluates the quality of life and health resource use and costs between the two alternatives, based on Gallone's research. A deterministic and probabilistic sensitivity analysis were carried out to characterize the uncertainty around the model's parameters.In the budget impact analysis Reducer is shown to be more expensive in the model's first two years, due to the gradual uptake in the market and the device's cost. Starting from the third year, assuming a maintenance of effectiveness, there is a savings in terms of resource absorption in direct health care costs arising from hospitalisations, emergency department accesses, coronarography and visits avoided.The budget impact analysis and cost-effectiveness model show that the Reducer device, despite an increase in resources absorbed in the first years of implementation and use, has the potential to result in increased quality of life in patients with refractory angina. These costs are largely offset in the short term by the improved clinical outcomes achievable leading to savings from the third year onward in the budget impact analysis and a dominance ratio in the cost-utility analysis.